MANAJEMEN KERAGAMAN, INKLUSI, DAN KEADILAN STRUKTURAL DI TEMPAT KERJA PERUSAHAAN INDUSTRI - Ahmad Jet Alamin A; Adrian K. Tarigan; Nurul Suci Anggraeni Nasution (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
In the era of globalization and digitalization, diversity, inclusion, and structural equity have become essential elements in the human resource management of industrial companies. Organizations are not only required to deliver high-quality products and services, but also to create a workplace that is welcoming, fair, and inclusive for all employees. This article examines the implementation of diversity management, inclusion, and structural equity in industrial workplaces using a literature review, policy comparisons, and case analysis. The study aims to understand the foundational concepts of DEI (Diversity, Equity, and Inclusion), evaluate the impact of DEI programs on company performance and competitiveness, and identify obstacles and best solutions for optimizing DEI—particularly structural fairness. The findings suggest that successful DEI implementation is driven by strong top management commitment, stakeholder involvement, inclusive training and development programs, and adaptive policies based on employees’ real needs (e.g., adjustments to personal protective equipment and working schedules). At the same time, challenges such as unconscious bias, resistance to change, differences in needs across worker groups, and limited resources must be addressed through open communication, data-driven decision-making, and transparent evaluation practices.